2021
DOI: 10.3390/act10030046
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Finite Element Modelling of Thermo-Visco-Plastic Styrene and Polyurethane Shape Memory Polymer Foams

Abstract: This paper presents nonlinear finite element (FE) models to predict time- and temperature-dependent responses of shape memory polymer (SMP) foams in the large deformation regime. For the first time, an A SMP foam constitutive model is implemented in the ABAQUS FE package with the aid of a VUMAT subroutine to predict thermo-visco-plastic behaviors. A phenomenological constitutive model is reformulated adopting a multiplicative decomposition of the deformation gradient into thermal and mechanical parts consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Typical PUFs demonstrated excellent thermal-responsive SMPs and shape controllability that play essential roles in preparing advanced biomedical devices, and for aerospace and textile applications. 5,6,8,11 In this study, the shape recovery of lignin-based PUFs was determined through a thermomechanical program (Figure 9a) by deforming the samples with axial compressive stretch in a range of 90 to 50% (Figure 9e). As the compressive stretch ratio reached 50% (from the original stretch ratio of 100%), the SEM images of PUF with 10% HPSKL showed that their microcellular structure decreased in size (Figure 9b,c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical PUFs demonstrated excellent thermal-responsive SMPs and shape controllability that play essential roles in preparing advanced biomedical devices, and for aerospace and textile applications. 5,6,8,11 In this study, the shape recovery of lignin-based PUFs was determined through a thermomechanical program (Figure 9a) by deforming the samples with axial compressive stretch in a range of 90 to 50% (Figure 9e). As the compressive stretch ratio reached 50% (from the original stretch ratio of 100%), the SEM images of PUF with 10% HPSKL showed that their microcellular structure decreased in size (Figure 9b,c).…”
Section: Resultsmentioning
confidence: 99%
“…PUFs have also demonstrated excellent thermoresponsive shape-memory properties (SMPs). 5,6 Due to this property, PUFs are at the forefront of the research area in responsive and gradient materials, including intelligent biomedical devices, aerospace materials, and textile applications. 7−12 As a result of urbanization and increasing population, the demand for these materials, and related chemical precursors, will keep growing in the following decades, requiring sustainable solutions in society at large.…”
Section: Introductionmentioning
confidence: 99%
“…In the first one, which is called the macro-scale, the physical quantities are transferred from the micro-scale level to the macro-scale level. Recently, Jarrah et al ( 2021 ) presented a VUMAT subroutine based on the constitutive model for the simulation of SMP foams. Additionally, Zolfagharian et al ( 2021 ) introduced a simple approach for the simulation of shape memory polymers fabricated by 4D printing technology.…”
Section: Modeling Of Smp Foamsmentioning
confidence: 99%
“…Shape memory polymers are a kind of material that can give one or more temporary shapes and can be returned to the initial state by external field stimulation, such as heat [ 1 , 2 ], electric [ 3 , 4 ], solvent [ 5 ], magnetic field [ 6 , 7 ], humidity [ 8 , 9 ], light [ 10 , 11 ] and pH [ 12 , 13 ]. It has a wide application prospect in biomedical [ 14 , 15 ], self-repairing [ 16 , 17 ], intelligent textile [ 18 , 19 ], drug controlled release [ 20 , 21 ], aerospace [ 22 , 23 ] and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal response of SMPU can be understood as follows: when the temperature is higher than the glass transition temperature ( T g ) of the soft segment or the melting temperature ( T m ) of the crystallization zone, the soft segment with a high elastic state will undergo large deformation, while the hard segment with glass state will prevent the molecular chain from sliding and produce internal resilience; when it is cooled to low temperature, the deformation will be fixed; when it is heated again above T g or T m of the soft segment, the hard segment will be deformed. Releasing the stored internal stress restores the material to its original shape [ 1 , 2 ]. It is the synergism between the soft segment and hard segment that makes polyurethane possess a shape memory effect (SME).…”
Section: Introductionmentioning
confidence: 99%